2020
DOI: 10.21103/article10(1)_oa12
|View full text |Cite
|
Sign up to set email alerts
|

Using Scanning Electron Microscopy and Atomic Force Microscopy to Study the Formation of Nanoparticles on Red Blood Cell Surface in Cervical Cancer Patients

Abstract: Background:In this study, we used scanning electron microscopy (SEM) and atomic force microscopy (AFM) to examine the changes in morphology of red blood cells (RBCs) and to investigate the nanoparticles (NPs) found on their surface in cervical cancer (CC) patients undergoing radiation therapy (RT).Methods and Results: We obtained smears of venous blood from 12 CC patients at the start, midway and at the end of external beam RT and then midway and at the end of brachytherapy. It was found that in CC patients, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
0
8
0
2
Order By: Relevance
“…It should be noted that blood circulating exosomes have been reported to contain distinguishable fractions of cell-free and cell-surface-associated vesicles [ 17 , 18 , 19 ]. It is known that circulating blood exosomes contact with blood cell plasma membranes.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that blood circulating exosomes have been reported to contain distinguishable fractions of cell-free and cell-surface-associated vesicles [ 17 , 18 , 19 ]. It is known that circulating blood exosomes contact with blood cell plasma membranes.…”
Section: Introductionmentioning
confidence: 99%
“…In the present, the studies of exosomes from plasma/serum in ovarian (21), breast (24), and colorectal cancers (28) have begun. A recent study has found that roughly two-thirds of the total blood extracellular vesicles of breast cancer patients exists in the blood cell-bound state (7,8). A thorough investigation of blood cell-bound EVs as significant players of cell-to-cell communication and as potential cancer biomarkers is therefore entirely justified.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, exosomes may deliver signals to induce EMT, migration, invasion, angiogenesis, and metastasis processes (2)(3)(4)(5)(6). It has been shown blood circulating exosomes contain two fractions of free and cell-surface-associated vesicles (7,8). Thus, the transport of vesicles is provided by both plasma exosomes and blood cell-surface-associated exosomes.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of the parameters of the distribution of diameters and surface area of erythrocytes shows that before RT, these parameters are less in patients with CC than in the control group, taking into account their altered forms. Earlier, using SEM studies [2,3], an increase in the number of dysmorphic erythrocytes was detected during RT, which was poorly studied using conventional blood analyzers, optical microscopy due to low resolution and lack of data analysis using machine learning (for example, using JMicroVision v1.2.7). And the use of this method of machine image recognition already at the beginning of RT allows us to observe changes in the morphology of erythrocytes of patients with CC (Fig.…”
Section: Figure 2b the Price-jones Curve In Pathologymentioning
confidence: 99%
“…Previously, images of the surface of erythrocytes were obtained at an increase of 100,000 times using a JEOL JSM-7800F SEM with a thermal field cathode of Schottky and with a Gentle Beam system at low accelerating voltages (1-2 kV) [2]. Increases of 1000 times in the work [3] were used to obtain statistical data on the morphology of erythrocytes of patients with CC during RT. The possibility of achieving this increase in magnification for SEM is easily realized and the images of erythrocytes are more informative than the images obtained on an optical microscope at the same magnification.…”
Section: Introductionmentioning
confidence: 99%